Gut lumen-leaked microbial DNA causes myocardial inflammation and impairs cardiac contractility in ageing mouse heart - Gao, Hong; Wang, Ke; Suarez, Jorge A.; Jin, Zhongmou; Rocha, Karina Cunha e; Zhang, Dinghong; Farrell, Andrea; Truong, Tyler; Tekin, Yasemin; Tan, Breanna; Jung, Hyun Suh; Kempf, Julia; et al. (Frontiers in Immunology, 2023)
Emerging evidence indicates the critical roles of microbiota in mediating host cardiac functions in ageing, however, the mechanisms underlying the communications between microbiota and cardiac cells during the ageing process have not been fully elucidated. Bacterial DNA was enriched in the cardiomyocytes of both ageing humans and mice. Antibiotic treatment remarkably reduced bacterial DNA abundance in ageing mice. Gut microbial DNA containing extracellular vesicles (mEVs) were readily leaked into the bloodstream and infiltrated into cardiomyocytes in ageing mice, causing cardiac microbial DNA enrichment. Vsig4+ macrophages efficiently block the spread of gut mEVs whereas Vsig4+ cell population was greatly decreased in ageing mice. Gut mEV treatment resulted in cardiac inflammation and a reduction in cardiac contractility in young Vsig4-/- mice. Microbial DNA depletion attenuated the pathogenic effects of gut mEVs. cGAS/STING signaling is critical for the effects of microbial DNA. Restoring Vsig4+ macrophage population in ageing WT mice reduced cardiac microbial DNA abundance and inflammation and improved heart contractility.